Stereoisomer-Independent Stable Blue Emission in Axial Chiral Difluorenol - Yu, Mengna; Jia, Xiong; Lin, Dongqing; Du, Xue; Jin, Dong; Wei, Ying; Xie, Linghai; Huang, Wei (Frontiers in Chemistry, 2021)
Bulky conjugated molecules with high stability is the prerequisite for the overall improvement of performance in wide-bandgap semiconductors. Herein, a chiral difluorenol, 2,2'-(9,9'-spirobi[fluorene]-2,2'-diyl)bis(9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol) (DOHSBF), is set as a desirable model to reveal the stereoisomeric effects of wide-bandgap molecules toward controlling photophysical behavior and improving thermal and optical stability. Three diastereomers are obtained and elucidated by NMR spectra. Interestingly, effect of modifying the stereo-centers is not observed on optical properties in solution, pristine film or post-treated film states. All the three diastereomers as well as the mixture exhibit excellent spectral stability without undesirable green emission. Therefore, this stereoisomer-independent blue-emitting difluorenol will be a promising candidate for the next-generation wide-bandgap semiconductors that would have extensive application in organic photonics.